Determination Of Dowry In The Community Of Indrapuri District, Aceh Besar District According To Islamic Law - Muhammad, Muhammad; Khairuddin, Khairuddin; Agustin Hanapi (Cita konsultindo, 2023)
The scholars agree that there is no maximum limit for the amount of dowry, but they differ on whether there is a minimum limit for the dowry. Then the reality is that in the culture of the people of Indrapuri District, it tends to set a burdensome dowry value. This type of research is categorized in the qualitative methods. The location of this research is in Indrapuri District, Aceh Besar District. Retrieval of data sources is done by feasibility (purposive sampling). Data analysis activities are carried out by analyzing data, organizing data, dividing it into manageable units, synthesizing to look for patterns, finding out what is meaningful and what is being researched and reporting systematically. The research results show that 1). The practice of the Community of Indrapuri Sub District, Aceh Besar District in the Determination of Dowry is to determine the amount of dowry determined by the community, the custom is always changing and varies according to changing times and the circumstances of prospective husbands and prospective wives. The practice of determining the dowry is carried out by the parents and themselves. Marriage, which begins with the determination of the dowry, is very important for the people of Indrapuri Subdistrict, Aceh Besar Regency, because it is one of the conditions for getting married. The dowry in the people of Indrapuri Subdistrict, Aceh Besar Regency is a symbol of the honor and prestige of the woman's family, the higher the dowry given by men will show the social status of women in the community, therefore everyone will compete to comply with the dowry obligations. 2). The analysis of Islamic law regarding the practice of determining dowry at Indrapuri susb district community of Aceh Besar district is that the practice of determining dowry that occurs is permissible in religion, because there is no specific law that forbids it. Plus, in Islam itself there are no absolute provisions regarding the amount of dowry, it's just that everything that is used as dowry is not excessive but must have value and benefits. Dowry does not have to be very large or very little. However, the point is that the dowry is prepared by the man as best he can and as well as possible.